Evaluasi RPS Rumpun Ilmu Ekonomi Pada Program Studi Pendidikan Ekonomi FKIP Unsri - Siti Fatimah Fatimah; Dewi Koryati; Dewi Pratita (Pendidikan Ekonomi FKIP Universitas Sriwijaya, 2020)
AbstractThis study aims to determine how effective the Semester Learning Plan (RPS) for the economics course in the Economic Education Study Program. The evaluation model used in this research is the CIPP Evaluation Model. Determination of the effectiveness of a RPS that is used is seen from the level of student understanding of economic science material which is interrelated with one another under the clump of economics. This research is a type of qualitative researach that uses the CIPP model by evaluating each component of the context, input, process and product to reaach an agreement in compiling an effective RPS between lecturers who teach courses in the economics cluster with students as learners. Sources of research data are RPS and lecturers who are teaching courses under theeconomics cluster. Primary data collection uses observation instruments, while secondary data is obtained through documentation and interviews. The observation data obtained werethen analyzed qualitatively. The results of the analysis of the CIPP model instrument from the context component are very effective, the input component is effective, the process component is effective and the product component is quite effective in the RPS for courses under the clump of economics to be used in learning activities.Keywords: RPS Evaluation, CIPP ModelAbstrakPenelitian ini bertujuan untuk mengetahui seberapa efektif Rencana Pembelajaran Semester (RPS) mata kuliah rumpun ilmu ekonomi pada Program Studi Pendidikan Ekonomi. Model evaluasi yang digunakan dalam penelitian ini yaitu Model Evaluasi CIPP. Penentuan keefektifan suatu RPS yang digunakan dilihat dari seberapa besar tingkat pemahaman mahasiswa terhadap materi ilmu ekonomi yang saling berkaitan satu sama lain dibawah rumpun ilmu ekonomi. Penelitian ini merupakan jenis penelitian kualitatif yang menggunakan model CIPP dengan mengevaluasi tiap komponen konteks, input, proses, dan produk untuk mencapai suatu kesepakatan dalam menyusun RPS yang efektif antara dosen yang mengampu mata kuliah didalam rumpun ilmu ekonomi dengan mahasiswa sebagai pembelajar. Sumber data penelitian adalah RPS serta dosen pengampu mata kuliah dibawah rumpun ilmu ekonomi. Pengumpulan data primer menggunakan instrumen observasi, sedangkan data sekunder diperoleh melalui hasil dokumentasi dan wawancara.Data hasil observasi yang diperoleh kemudian dianalisis secara kualitatif. Hasil analisis instrumen model CIPP dari komponen context sangat efektif, komponen input efektif, komponen process efektif dan komponen product cukup efektif RPS mata kuliah dibawah rumpun ilmu ekonomi untuk digunakan dalam kegiatan pembelajaran.Kata Kunci: Evaluasi RPS, Model CIPP